The dominance of directors, audit committee effectiveness and accounting conservatism: Malaysian evidence / Mohd Shatari Abd Ghafar - Abd Ghafar, Mohd Shatari (Institute of Graduate Studies, UiTM, 2012)
This study uses the alignment effect hypothesis from agency theory and the entrenchment hypothesis to examine the firms’ financial reporting conservatism relative to the effectiveness of their audit committees and the dominance of directors. The study is also extended to determine the association of audit committee effectiveness and directors’ dominance and their linkage to the firms’ degree of accounting conservatism. The proxy for audit committee effectiveness in this study are audit committee independence, accounting financial expertise and diligence. Meanwhile, the proxies for directors’ dominance are executive director’s dominance, family director’s dominance and audit committee shareholding. Using Khan and Watts’s (2009) C_SCORE measures of accounting conservatism, the C_SCORE of 795 firms-year observation from Bursa Malaysia main board is calculated. The findings reveal that only professional accounting expertise and audit committee diligence are significant to explain the variations in the firms’ financial reporting conservatism. The results also suggest that executive ownership and CEO duality are detrimental to firms’ degree of accounting conservatism.